Грбовничето на Виргил Солис и неговото влијание врз раните модерни илирски грбовници - Virgil Solis’ Wappenbüchlein and its impact on Early Modern Illyrian Armorials - Filipovic, Emir (Македонски хералд - Macedonian Herald, 2023)
This paper examines the relationship between the Wappenbüchlein, published in Nuremberg in 1555 by German printmaker Virgil Solis, and the collection of early modern Illyrian armorials, the oldest of which can be dated to the end of the sixteenth century. After a brief introductory overview of the artist’s life, the author then tries to establish the role and significance of his work as one of the early sources for Illyrian heraldry. Along with books of other German authors, such as Ulrich Richental, Conrad Grünenberg and Sebastian Münster, which were published earlier, Solis’ Wappenbüchlein served as a direct template for authors of the first Illyrian armorials. This is confirmed by the obvious similarities in the title, internal composition and the arrangement of the arms that exist in this work and the oldest known Illyrian armorial from 1595. Although the importance of Solis’ Wappenbüchlein had already been recognized in scholarly literature, it has never been analysed on its own merit as a role model for Illyrian armorials. Therefore, the intention of this paper is to attempt to determine with more precision the place and role of this work in the establishment and development of Illyrian heraldry.